Pioneer trails West. - Worcester, Don (Caxton Printers Caldwell, Odaho, 1985)
Among the trails covered are the Trail of Tears and cowboy trails which passed through Oklahoma, such as the Chisholm Trail, the Shawnee Trail, and the Western Trail.
Includes Index
Keywords: History; West (U.S.)